The Integration of Science and Religion: Analysing Research Paradigms in Indonesian State Islamic Universities through a Lakatosian Lens - Muslih, Mohammad; Taqiyuddin, Muhammad (Afkar: Jurnal Akidah dan Pemikiran Islam, 2025)
Practical questions may arise regarding the feasibility of conducting research using the Islamic paradigm. However, within Indonesian State Islamic universities (UIN), particularly those established by the government, numerous questions have already been answered. The fundamental concept of the ‘integration of science and religion’ has been successfully implemented for several years in numerous UINs. Several scholarly works have emerged from this conventional paradigm. This article aims to improve the comprehension of research articles published by the UIN Bandung, known as UIN Sunan Gunung Djati Bandung. The qualitative study focuses on select works that employ this paradigm as subjects of analysis. The study design employs a literary-survey methodology, including classified lecture articles, which are subsequently examined from a Lakatosian philosophical perspective on scientific paradigms. The findings reveal that some research articles can be categorised based on their methodological coherence, aligning with the Islamic paradigm, which is denominated as the integration of science and religion. Regardless of the strict correspondence percentage with the Lakatosian paradigm, the results can be classified as follows: 1) auxiliary hypotheses, 2) justification and 3) quasi-scientific integration. Further insights indicate that the Wahyu Memandu Ilmu (WMI), hereinafter called ‘Revelation Guiding Science’ paradigm, is an evolution of the integration–interconnection concept initiated by M. Amin Abdullah.